2018
DOI: 10.1021/acs.macromol.8b01953
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Block Copolymer Domain Spacing and Morphology on the Cation Structure of Ionic Liquid Additives

Abstract: We find that the topology of phase diagrams for block copolymer/ionic liquid (IL) blends and the scaling of the phase-separated domains are significantly influenced by the cation structure of the IL. We have varied the cation structure of bis(trifluoromethane sulfonyl)imide ILs and investigated the influence of these changes on the thermodynamics of blends with polystyrene-b-poly(methyl methacrylate). Effective χ parameters (χ eff ) were determined and used to plot phase diagrams, where significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 45 publications
3
18
3
Order By: Relevance
“…For weakly charged polyelectrolytes with small inorganic ions, the effect of electrostatic screening was also incorporated into the theory of Leibler . This model predicts decreases in the incompatibility between two blocks upon the addition of small amounts of ILs, but experimental observations for a mixture of a diblock copolymer and an IL suggest that the two blocks become significantly immiscible. Moreover, the volume of ILs is comparable to or even larger than the monomer volumes, but this feature has been largely ignored in existing theories for small inorganic ions. Thus, clarification of the driving force for the phase separation of IL-containing block copolymers is greatly needed and is likely to bridge the gap between theory and experiment.…”
Section: Introductionmentioning
confidence: 99%
“…For weakly charged polyelectrolytes with small inorganic ions, the effect of electrostatic screening was also incorporated into the theory of Leibler . This model predicts decreases in the incompatibility between two blocks upon the addition of small amounts of ILs, but experimental observations for a mixture of a diblock copolymer and an IL suggest that the two blocks become significantly immiscible. Moreover, the volume of ILs is comparable to or even larger than the monomer volumes, but this feature has been largely ignored in existing theories for small inorganic ions. Thus, clarification of the driving force for the phase separation of IL-containing block copolymers is greatly needed and is likely to bridge the gap between theory and experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the power law dependence of domain spacing on the composition of BCP/IL blends was used widely. But the power-law index depends irregularly on the selectivity of IL, the morphology of block copolymer, and the compositional block ratio within the same morphology, without clear physical meaning. …”
Section: Discussionmentioning
confidence: 99%
“…These authors found that the topology of the phase diagrams of the block copolymer/IL blends and the scaling of the phase-separated domains are significantly influenced by the cation structure of the IL. The balance of Coulombic and van der Waals interactions also influences the topology of the phase diagrams …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these features that do not exist or are less common in the case of inorganic salts may tarnish the reputation of the existing thermodynamic theories for polymer electrolytes. Among others, the development of the theoretical frameworks and computationally tractable thermodynamic models that consider the microphase separation of IL‐containing block copolymers would be expected to come according to future perspectives regarding smart materials with a mixture of ILs and block copolymers 33 and to surging reports from various experimental groups 10,34–58 …”
Section: Introductionmentioning
confidence: 99%